Energy dependence and fluctuations of anisotropic flow in Pb-Pb collisions at √ˢɴɴ=5.02 and 2.76 TeV - Acharya, S.; Torales-Acosta, F.T.; Adamovã, D.; Adolfsson, J.; Aggarwal, M.M.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahn, S.U.; Aiola, S.; Akindinov, A.; et al. (Springer Verlag, 2018)
Measurements of anisotropic flow coefficients with two- and multi-particle cumulants for inclusive charged particles in Pb-Pb collisions at √ˢɴɴ = 5.02 and 2.76TeV are reported in the pseudorapidity range |n| < 0.8 and transverse momentum 0.2 < Pᴛ < 50 GeV/c. The full data sample collected by the ALICE detector in 2015 (2010), corresponding to an integrated luminosity of 12.7 (2.0) µb¯¹ in the centrality range 0-80%, is analysed. Flow coefficients up to the sixth flow harmonic (v₆) are reported and a detailed comparison among results at the two energies is carried out. The Pᴛ dependence of anisotropic flow coefficients and its evolution with respect to centrality and harmonic number 𝓃 are investigated. An approximate power-law scaling of the form vn(Pᴛ) ~ Pᴛᶯ⁻³ is observed for all ow harmonics at low Pᴛ (0.2 < Pᴛ < 3 GeV/c). At the same time, the ratios vɳ/v֋ᶯ⁻ᵐ are observed to be essentially independent of Pᴛ for most centralities up to about Pᴛ = 10 GeV/c. Analysing the differences among higher-order cumulants of elliptic flow (v₂), which have different sensitivities to flow fluctuations, a measurement of the standardised skewness of the event-by-event v₂ distribution P(v₂) is reported and constraints on its higher moments are provided. The Elliptic Power distribution is used to parametrise P(v₂), extracting its parameters from ts to cumulants. The measurements are compared to different model predictions in order to discriminate among initial-state models and to constrain the temperature dependence of the shear viscosity to entropy-density ratio.
Keywords: Heavy Ion Experiments; https://purl.org/pe-repo/ocde/ford#1.03.03